(untitled) (Iranian Journal of Kidney Diseases, 2019)
A 6-year-old Syrian boy presented with complaints of facial dysmorphism and difficulty of walking. He had coarse face, macrocephaly, pectus carinatum, x-bain deformity, kyphosis, corneal clouding, and claw hand deformity. Galactose-6 sulphatase enzyme level was 0.1 nmol/mg.17 h (reference range, > 68 nmol/mg.17 h), compatible with Morquio syndrome. On laboratory examinations, potassium level was 2.9 mmol/L (reference range, 3.5 mmol/L to 5.1 mmol/L), sodium level was 130 mmol/L (reference range, 135 mmol/L to 148 mmol/L), and chloride level was 92 mmol/L (reference range, 101 mmol/L to 109 mmol/L). Blood pH was 7.5 and bicarbonate level was 31 mEq/L. Urine sodium and chloride levels were high. Arterial blood pressure was normal and these findings were consistent with Bartter syndrome. This is the first report of a patient with the association of Bartter syndrome and mucopolysaccharidosis type 4A, which was thought to be coincidental.